A study of vibration mode shape and noise emission of a rectangular panel - Lee, Wai Neng (1999)
Contemporary procedures for the determination of structural vibration, relies on vast computer storage with excessive time for manipulation. This thesis resorts to an investigation of the vibration and noise radiation of flat panels*. It avoids prolong calculation and presents novel approximate formulae devised in this work. An outline of some of the formulae is given. In vibration of Plates, an approximate method using a teclmique of 'length equivalencing' reduces and simplifies the classical solution procedure. A method of determining the local modes of a rectangular plate with a number of symmetrical parallel stiffeners is also given. This is achieved by observing linearity in the modal configuration. Hitherto, this phenomenon has not been reported in research literature. The purpose of investigating the noise radiation of the plates was to determine the noise level in the proximity of the plate within a room or enclosure. The room of industrial/manufacturing areas is reverberant hence its acoustic properties must be measured before prediction of the noise level is possible. The classical property is the measurement of Reverberation Time CRT). In this investigation, a novel technique of predicting a family of decay curves of varying absorption coefficient, ex and fitting them with the actual decay measured has been calculated. Thus a protracted advance into the detailed conventional acoustic properties was alleviated.